2016
DOI: 10.3389/fevo.2016.00041
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Soil Insects across Three Spatial Scales in Agricultural Grassland

Abstract: The effects of specific environmental factors on abundance and distribution of some individual soil insect taxa is known, but how scale influences spatial distribution is less well evaluated, particularly at the community level. However, given that many soil insects are pests or beneficial natural enemies, and that collectively they play a role in soil processes, this information is of potential value for predictive modeling and in furthering our understanding of soil ecology and management. The objectives of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…haplotype 4) are common throughout the study site, and that AMOVA results suggest a panmictic population with little evidence of spatial structuring [in accordance with Benefer et al . () who, in a broader assessment, found little evidence of scale or space affecting tipulid larvae presence/absence in general], a lack of dispersal ability in T. paludosa in general does not appear to be the case, at this scale of study at least. For example, field 1 and field 19 are separated by a distance of approximately 1.6 km but share haplotype 1.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…haplotype 4) are common throughout the study site, and that AMOVA results suggest a panmictic population with little evidence of spatial structuring [in accordance with Benefer et al . () who, in a broader assessment, found little evidence of scale or space affecting tipulid larvae presence/absence in general], a lack of dispersal ability in T. paludosa in general does not appear to be the case, at this scale of study at least. For example, field 1 and field 19 are separated by a distance of approximately 1.6 km but share haplotype 1.…”
Section: Discussionmentioning
confidence: 72%
“…(), who reported 4% of larvae to be this species in a survey of 75 agricultural grass fields in Northern Ireland. Adults were not directly surveyed in the present study, although, based on observational data, both species were abundant aboveground, which could suggest that there are species‐specific oviposition preferences and/or differences in dispersal ability (Blackshaw et al ., ; Benefer et al ., ). Although the limited data from surveys in U.K. agricultural grassland suggest T. oleracea may not be present in damaging proportions, in North America this species is becoming more common in turfgrass (Rao et al ., ) and so it is important to be able to separate damaging species reliably.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Up to now, examples of grid-based sampling at multiple spatial scales come e.g. from a sampling campaign for soil insects, where Benefer et al (2016) showed detailed maps of the distribution of various taxa on sites measuring about 1 9 1 km. Similar approaches were used in the pan-European project ''Greenveins'' for insects and birds (Dormann et al 2007b;Le Féon et al 2010), and grid-based approaches in general are widely employed in biodiversity monitoring schemes (e.g.…”
Section: Introductionmentioning
confidence: 99%